Introducing English Grammar and Vocabulary by Applying Direct Method for the Students of GMIT Petra Kefamenanu - Napitupulu, Merlin Helentina; Semiun, Thresia Trivict; Wihelmina, Maria Wisrance; Simarmata, Justin Eduardo (Talenta Publisher, 2021)
Introducing English Grammar and Vocabulary by applying Direct Method for the students of GMIT Petra Kefamenanu aimed to attract the students’ interesting of English learning and improve their ability on learning English. This community service activity had been held for one month, once a week in 90 minutes for every meeting. There were primary students who joined this community service activity which consisted of the students from elementary school at GMIT Petra Kefamenanu. The students were introduced and taught English by applying Direct method with various fun activities to make the students feel enjoy and joyful. The students learnt English Grammar and Vocabulary enthusiastically and the students practiced English step by step. This community service activity affected the students’ ability on learning English. By introducing English Grammar and Vocabulary, the students got knowledge about grammar and vocabulary. From this activity, it could be concluded that the students’ knowledge and ability about grammar and vocabulary has increased after introducing of English grammar and vocabulary by applying Direct Method.